2098778
contestada

Help please this math is wack I am not having a good time
d(1)=3
d(n)=d(n−1)−14
3rd term in the sequence


Respuesta :

Answer:

The third term is  -25.

Step-by-step expanation:

d(1)=3

From this equation, we know the first term is 3.

d(n)=d(n−1)−14

This looks like a recursive formula. It is used to find the next term.

n is the variable for the term number that you are solving for.

d(n-1) is the term value before the what you are looking for.

To find the 2nd term, use the formula and substitute values known:

d(n)= d(n−1)−14

d(2) = d(2-1) - 14

d(2) = d(1) - 14

We know d(1)=3

d(2) = 3 - 14

d(2) = -11

Find the third term using the same method:

d(n) = d(n−1)−14

d(3) = d(3−1)−14

d(3) = d(2)−14

d(3) = -11 - 14

d(3) = -25

Answer:

The third term is  -25.

Step-by-step expanation:

d(1)=3

From this equation, we know the first term is 3.

d(n)=d(n−1)−14

This looks like a recursive formula. It is used to find the next term.

n is the variable for the term number that you are solving for.

d(n-1) is the term value before the what you are looking for.

To find the 2nd term, use the formula and substitute values known:

d(n)= d(n−1)−14

d(2) = d(2-1) - 14

d(2) = d(1) - 14

We know d(1)=3

d(2) = 3 - 14

d(2) = -11

Find the third term using the same method:

d(n) = d(n−1)−14

d(3) = d(3−1)−14

d(3) = d(2)−14

d(3) = -11 - 14

d(3) = -25

ACCESS MORE